Early detection of leprosy by examination of household contacts, determination of serum anti-PGL-1 antibodies and consanguinity - Renata Bazan-Furini; Ana Carolina F Motta; João Carlos L Simão; Daniela Chaves Tarquínio; Wilson Marques Jr; Marcello Henrique N Barbosa; Norma Tiraboschi Foss (Memorias do Instituto Oswaldo Cruz, 2011)
A cross-sectional clinical trial in which the serum anti-phenolic glycolipid (anti-PGL-1) antibodies were analysed in household contacts (HHC) of patients with leprosy as an adjunct early leprosy diagnostic marker was conducted. The families of 83 patients underwent clinical examination and serum anti-PGL1 measurement using enzyme-linked immunosorbent assay. Of 320 HHC, 98 were contacts of lepromatous leprosy (LL), 80 were contacts of borderline lepromatous (BL), 28 were contacts of borderline (BB) leprosy, 54 were contacts of borderline tuberculoid (BT), 40 were contacts of tuberculoid (TT) and 20 were contacts of indeterminate (I) leprosy. Consanguinity with the patients was determined for 232 (72.5%) HHC. Of those 232 contacts, 183 had linear consanguinity. Forty-nine HHC had collateral consanguinity. Fifty-eight contacts (18.1%) tested positive for anti-PGL1 antibodies. The number of seropositive contacts based on the clinical forms of the index case was 17 (29.3%) for LL, 15 (25.9%) for BL, one (1.7%) for BB, 14 (24.1%) for BT, three (5.2%) for TT and eight (13.7%) for I. At the one year follow-up, two (3.4%) of these seropositive contacts had developed BT leprosy. The results of the present study indicate that the serum anti-PGL-1 IgM antibody may be useful for evaluating antigen exposure and as a tool for an early leprosy diagnosis in HHC.